PTH-052 Does throat spray in combination with intravenous sedation/analgesia for elective gastroscopy increase respiratory complications?. (June 2019) - Patel, Mehul; Akintimehin, Abisoye; Gunasingam, Nishmi; Kumar, Mayur; Haji, Amyn; Hayee, Bu'Hussain
Abstract : Introduction: Safe sedation practice is a recognised cornerstone of high-quality endoscopy. There are concerns that local anaesthetic throat spray (TS) in combination with intravenous sedative and analgesic agents (ISAAs) can precipitate respiratory complications, specifically, aspiration pneumonia. Current BSG standards for upper gastrointestinal endoscopy recommend 'caution should be exercised' in using agents combined with TS but acknowledges the paucity of evidence for this, with the few relevant studies being performed several decades ago. Methods: A retrospective, two-centre cohort study was performed. Only diagnostic, outpatient gastroscopies (OGDs) performed 2013–2018 were reviewed. Patients residing in a postcode region (definite or possible) outside of the catchment of the two centres were excluded from final analysis. Endoscopy reports and electronic patient records were reviewed to identify all patients who presented to hospital within 30 days of their procedure to determine the underlying reason for this. Results: 5, 803 OGDs met the inclusion criteria. 148 (2.6%) patients presented to hospital within 30 days of procedure, 17 (0.3%) were due to potential respiratory complications (pneumonia, respiratory tract infection and infective exacerbation of COPD). Choice of drug included: TS 3163 (54.5%); TS+midazolam 1508 (26%); TS+fentanyl 28 (0.5%); TS+dual agent 382 (6.6%) and non-TS 722 (12.4%). Only TS and TS+analgesic/sedative groups were compared. There was no significant difference in the rate of respiratory complications between the two groups (p=1.0, two-sided Fisher's Exact Test). 12/17 respiratory complications occurred in the TS group. Procedure discomfort scores were similar in this group when compared to the TS and additional agent group. Conclusions: While safe sedation practice should remain the cornerstone of management and clinicians should continue to exercise caution in patients with respiratory comorbidities, inpatients and therapeutic procedures, the combination of TS+ISAAs does not increase the risk of respiratory complications following elective diagnostic OGD.